Saberes docentes e a Geografia Urbana Escolar - OLIVEIRA, Karla Annyelly Teixeira de (2008)
This dissertation investigated the development process education of a Geography teacher. The focus of this research was on the composition of the teacher s knowledge about "urban Geography school". It used formation conception of the teacher as a continuum, as composed by teacher s background, his initial education at the University and by his work at school. When designing the school knowledge , "urban Geography school" as a teacher s knowledge the research development came from the following guiding questions: what is the role of teacher formation in the building of the teacher s knowledge about urban Geography school ? How does city is taught in Geography courses at University? How does city is taught in Geography as a school subject? From the content city , in the case study based on qualitative approach, we investigated the formation trajectory of five Geography teachers that studied at Goiás Universities: Federal, Catholic and State. About University training we investigated: the aspirations of teachers in relation to the University, the course of Geography and the teaching profession, their conditions to conduct the course, as well as their assessement about their formation on the content city at University. We have identified how the city is taught in Geography courses, at the University. At School, the research examined how teachers teach the content city , the sources and criteria used to select the content being taught and their thoughts about the teaching of the given content. Part of the results obtained during the research corroborate those listed on the theoretical teacher formation, and the results raised in other studies. It was found that experiences as student and teacher of basic education incorporate teachers´s knowledge, the university education is desired with the intention of building scientific knowledge and have a university degree, the formation about city content, the Urban Geography, is assessed as positive. To form the conceptual thinking on the urban is the main goal of the Geography course about city. The practice of the Geography teacher at school is essentially in the classroom, with long work hours and high number of classes, the school textbook is used as prescribed curriculum, the city is more a Geography as a school subject content, although it is addressed so indirect in all lessons. The teaching practice has also elements of innovation in relation to the established culture expressed: in the reading teachers consider the reality of the student, in the search of association between the student s education and background, aiming at taking the place he/she lives as an object of study and education in school, and mainly in the identification of the specificity on urban Geography academic and school. In the research we identified that the formation of a geography teacher, in order to build their knowledge on the urban school geography is marked by a series of precariousness that go from the choice of profession, the route universitary formation, to work conditions at school. There is a broad movement, in that the "urban Geography school " taught is understood from the elements set: the formation of the Geography teacher at University, the teacher´s working conditions and their personal aspirations. It must consider this elements together and take into account the role of the state and the socioeconomic structure in this process and the role of science and knowledge, as a discourse of legitimacy and criticism of this reality.